Diagnostic Yield of Electroanatomic Voltage Mapping in Guiding Endomyocardial Biopsies. Issue 13 (29th September 2020) - Casella, Michela; Dello Russo, Antonio; Bergonti, Marco; Catto, Valentina; Conte, Edoardo; Sommariva, Elena; Gasperetti, Alessio; Vettor, Giulia; Tundo, Fabrizio; Sicuso, Rita; Rizzo, Stefania; Mushtaq, Saima; et al.
Abstract : Background: Electroanatomic voltage mapping (EVM) is a promising modality for guiding endomyocardial biopsies (EMBs). However, few data support its feasibility and safety. We now report the largest cohort of patients undergoing EVM-guided EMBs to show its diagnostic yield and to compare it with a cardiac magnetic resonance (CMR)–guided approach. Methods: We included 162 consecutive patients undergoing EMB at our institution from 2010 to 2019. EMB was performed in pathological areas identified at EVM and CMR. CMR and EVM sensitivity and specificity regarding the identification of pathological substrates of myocardium were evaluated according to EMB results. Results: Preoperative CMR showed late gadolinium enhancement in 70% of the patients, whereas EVM identified areas of low voltage in 61%. Right (73%), left (19%), or both ventricles (8%) underwent sampling. EVM proved to have sensitivity similar to CMR (74% versus 77%), with specificity being 70% and 47%, respectively. In 12 patients with EMB-proven cardiomyopathy, EVM identified pathological areas that had been undetected at CMR evaluation. Sensitivity of pooled EVM and CMR was as high as 95%. EMB analysis allowed us to reach a new diagnosis, different from the suspected clinical diagnosis, in 39% of patients. The complications rate was low, mostly related to vascular access, with no patients requiring urgent management. Conclusions: EVM proved to be a promising tool for targeted EMB because of its sensitivity and specificity for identification of myocardial pathological substrates. EVM was demonstrated to have accuracy similar to CMR. EVM and CMR together conferred a positive predictive value of 89% on EMB. Abstract : Supplemental Digital Content is available in the text.